Gauging the effect of feedback from QSOs on their host galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - de Oliveira, Bruno Dall'Agnol; Storchi-Bergmann, Thaisa
Abstract: Often associated with the regulation of star formation in galaxies, active galactic nuclei (AGN) play a fundamental role in the evolution of galaxies through their feedback effects. To investigate the impact of these effects, we analysed the optical emission-line properties of 8 type II AGNs with bolometric luminosities LBol > 10 45 erg s −1, using integral field spectroscopy (IFS) observations with Gemini Multi-Object Spectrograph (GMOS). The gas kinematics was obtained by fitting Gaussian components to the profiles of the emission lines of the ionized gas. Using only the broadest component – that we associate with the gas in outflow – we calculated the mass outflow rate ( Ṁout ), finding values of up to 10 M⊙ yr −1 . The outflow kinetic power ( Ėout reaches maximum values between 10 41 and 10 43 erg s −1, which correspond to feedback efficiencies of ∼0.001−0.1 % of Lbol . These values are below that required to quench the star formation during the evolution of galaxies in simulations and analytical models. We also investigated the effect of uncertainties on the values of the physical quantities used in the calculations – such as the electron density – on the final values of Ṁout and Ėout .